Study of Si(Al)CN functionalized carbon nanotube composite as a high temperature thermal absorber coating material - Asok, Deepu (Kansas State University, 2013)
Carbon nanotubes (CNT) and polymer-derived ceramics (PDC) have gained considerable research attention due to their unique structure and physical properties. Carbon nanotubes are known for their exceptional mechanical (Young’s modulus= 1 TPa) and thermal properties (thermal conductivity = 4000 W/m.K). However, CNTs tend to lose their unique -sp2 carbon structure and cylindrical geometry at temperatures close 400°C in air. PDC, which are obtained by the controlled degradation of certain organosilicon polymers however exhibit high temperature stability (upto approx. 1400 °C). To this end, a hybrid composite material consisting of PDC functionalized CNT is of interest as it can combine the unique physical properties of the two materials for applications requiring operation under harsh conditions. Here, we report synthesis and chemical characterization of an Al-modified polysilazane polymer, which was later utilized to functionalize the outer surfaces of four commercially available CNTs. This polymer-CNT composite upon heating in nitrogen environment resulted in Si(Al)CN-CNT ceramic composite. The composite was characterized using a variety of spectroscopic methods such Raman, FTIR and electron microscopy. The thermal stability of the ceramic composite was studied by use of Thermogravimetric analysis (TGA) that showed an improvement in the thermal stability compared to bare nanotubes. Further, we also demonstrate that a stable dispersion of the composite in organic solvents such as toluene can be spray coated on a variety of substrates such as copper disks and foils. Such coatings have application in high energy laser power meters. This research opens new avenues for future applications of this novel material as coatings on surfaces that require both good thermal properties and protection against degradation in high temperature environments. We also suggest the future use of this material as an electrode material in high electrochemical capacity rechargeable batteries.
Keywords: Polymer derived ceramics; Carbon nanotubes; Composite; Coating; Materials Science (0794); Mechanical Engineering (0548); Nanoscience (0565); Nanotechnology (0652)